Cruel Intentions: liberal logics and processes of international criminalization - Han, Y; Nantermoz, O (Oxford University Press, 2022)
The prohibition and prosecution of core international crimes are understood as a liberal response to particularly cruel acts that shock the conscience of humanity. But what is the nature of this cruelty and how does it relate to liberalism? Rather than seeing liberalism as monolithic, we examine the different relationships between liberal logics and cruelty and how they manifest in processes of international criminalization. We develop a three-pronged typology of liberalism(s) based on their constitutive relationship to cruelty. The first logic expands upon Judith Shklar's theory of “Liberalism of Fear” that sees cruelty as detrimental to liberal society, foregrounding particularly acute forms of physical and affective cruelty in liberal politics and law; the second logic, “Racial Liberalism,” understands cruelty as a condition of possibility for the liberal order built on the exploitation of racialized others; and the third conceives of cruelty as produced by the market logic of trade-offs, referred to as “Sacrificial Liberalism.” Based on this framework, we examine two processes of international criminalization: the crime of genocide (widely considered to be the “crime of crimes” and thus an emblematic case of criminalized cruelty directed against collective identities) and the crime of aggression (which followed a more complicated criminalization trajectory). By tracing how different liberal logics interrelate, come into tension, and thus shape the processes of international criminalization, we not only illuminate the shifting legitimations and normative priorities of the liberal international order but also confront the normative value of criminalizing cruelty.